Temporal muscle thickness is an independent prognostic marker in patients with progressive glioblastoma: translational imaging analysis of the EORTC 26101 trial. Issue 12 (1st August 2019) - Furtner, Julia; Genbrugge, Els; Gorlia, Thierry; Bendszus, Martin; Nowosielski, Martha; Golfinopoulos, Vassilis; Weller, Michael; van den Bent, Martin J; Wick, Wolfgang; Preusser, Matthias
Abstract: Background: Temporal muscle thickness (TMT) was described as a surrogate marker of skeletal muscle mass. This study aimed to evaluate the prognostic relevance of TMT in patients with progressive glioblastoma. Methods: TMT was analyzed on cranial MR images of 596 patients with progression of glioblastoma after radiochemotherapy enrolled in the European Organisation for Research and Treatment of Cancer 26101 trial. An optimal TMT cutoff for overall survival (OS) and progression-free survival (PFS) was defined in the training cohort ( n = 260, phase II). Patients were grouped as "below" or "above" the TMT cutoff and associations with OS and PFS were tested using the Cox model adjusted for important risk factors. Findings were validated in a test cohort ( n = 308, phase III). Results: An optimal baseline TMT cutoff of 7.2 mm was obtained in the training cohort for both OS and PFS (area under the curve = 0.64). Univariate analyses estimated a hazard ratio (HR) of 0.54 (95% CI: 0.42, 0.70; P < 0.0001) for OS and an HR of 0.49 (95% CI: 0.38, 0.64; P < 0.0001) for PFS for the comparison of training cohort patients above versus below the TMT cutoff. Similar results were obtained in Cox models adjusted for important risk factors with relevance in the trial for OS (HR, 0.54; 95% CI: 0.41, 0.70; P < 0.0001) and PFS (HR, 0.47; 95% CI: 0.36, 0.61; P < 0.0001). Results were confirmed in the validation cohort. Conclusion: Reduced TMT is an independent negative prognostic parameter in patients with progressive glioblastoma and may help to facilitate patient management by supporting patient stratification for therapeutic interventions or clinical trials.